Hepatic Encephalopathy: Pharmacological Therapies Targeting Ammonia - Rahimi, Robert S.; Rockey, Don C. (Seminars in Liver Disease, 2016)
Hepatic encephalopathy (HE) is a major complication in patients with decompensated cirrhosis, leading to higher readmission rates causing a profound burden of disease and considerable health care costs. Because ammonia is thought to play a crucial role in the pathogenesis of HE, therapies directed at reducing ammonia levels are now being aggressively developed. Ammonia scavengers such as AST-120 (spherical carbon adsorbent), glycerol phenylbutyrate, sodium phenylacetate or sodium benzoate, and ornithine phenylacetate have been used to improve HE symptoms. A new approach, bowel cleansing with polyethylene glycol 3350, appears to be a promising therapy, with a recent study demonstrating a more rapid improvement in overt HE (at 24 hours after treatment) than lactulose. Extracorporeal devices, although now used primarily in research settings, have also been utilized in patients with refractory HE, but are not approved for clinical management.
Keywords: AST-120; cirrhosis; glycerol phenylbutyrate; lactulose; molecular adsorbent recirculating system; ornithine phenylacetate; benzoate; polyethylene glycol